Using modern computer technology for automatization of production processes - Бодненко, Тетяна Василівна (Technology audit and production reserves, 2015)
Using of modern computer technology to automate production processes will increase productivity and significantly reduce production time product at work. For optimal organization of production processes using computer technology needed them the right choice. It is caused by the specific activities of enterprises of different types of economic activity, ownership and diversity of the tasks of economic analysis, the solution of which is effectively the effective management of the enterprise in the market, which, in turn, are characterized by rapid change of environmental factors, uncertainty and risk. Because modern production - a complex, multi-faceted, multi-functional system, which is in the process of improvement and adaptation to external factors. To succeed output required to implement a strategic plan for industrial automation. Nowadays there are many systems to automate production processes. In this regard, we choose a system for the enterprise: the class system, for example, ERP-systems can be installed in industrial enterprises and organizations in the service sector, for medium-sized businesses do not need a powerful functionality of these systems, so usually choose MRP II system; system manufacturer (western or domestic); someone who will carry out the introduction of (developer or consultant). Between the preferred systems of automation of production processes identified: Sarah system (Computer Aided Process Planning), system of CAD (Computer Aided Design - design using computer programs), class CAE applications (numerical simulation of heat and mass transfer processes, physical and chemical reactions and metallurgical processes, analysis of electric fields), the system ERP (Enterprise Resource Planning - Enterprise Resource). There are examples of application of T-FLEX CAD 3D. These studies provide an opportunity to improve computer technology to automate production processes.